2011
DOI: 10.1002/dneu.20844
|View full text |Cite
|
Sign up to set email alerts
|

Development of NMDA NR2 subunits and their roles in critical period maturation of neocortical GABAergic interneurons

Abstract: The goals of this research are to 1) determine the changes in the composition of NMDA receptor (NMDAR) subunits in GABAergic interneurons during critical period (CP); and 2) test the effect of chronic blockage of specific NR2 subunits on the maturation of specific GABAergic interneurons. Our data demonstrate that: 1) The amplitude of NMDAR mediated EPSCs (EPSCsNMDAR) was significantly larger in the postCP group. 2) The coefficient of variation (CV), τdecay and half-width of EPSCsNMDAR were significantly larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 162 publications
(239 reference statements)
4
35
0
Order By: Relevance
“…These results suggest that while the cells are still alive, their developmental maturation may be affected. Similar results were recently obtained using a mouse line expressing GFP in all GABAergic neurons (252). In this study, using an NR2A-preferring antagonist, the authors showed that prolonged blockade of NR2A-containing receptors in vivo during the critical period of plasticity in the barrel cortex produced a decrease in PV expression and an alteration of fast-spiking-mediated inhibitory postsynaptic currents onto principal neurons.…”
Section: Nox2 In Schizophreniasupporting
confidence: 71%
See 3 more Smart Citations
“…These results suggest that while the cells are still alive, their developmental maturation may be affected. Similar results were recently obtained using a mouse line expressing GFP in all GABAergic neurons (252). In this study, using an NR2A-preferring antagonist, the authors showed that prolonged blockade of NR2A-containing receptors in vivo during the critical period of plasticity in the barrel cortex produced a decrease in PV expression and an alteration of fast-spiking-mediated inhibitory postsynaptic currents onto principal neurons.…”
Section: Nox2 In Schizophreniasupporting
confidence: 71%
“…PV + neurons in the rodent PFC express high levels of functional NMDARs during the first 3-4 postnatal weeks, and the activity of these receptors is necessary for the normal development of their characteristic fast-spiking (107,236,246,252). Interestingly, NMDARs in these neurons have a different subunit composition than that found in neighboring pyramidal neurons, with NR2A/NR2B ratios of 5:1 in PV + neurons and 1:1 in pyramidal neurons (107,246).…”
Section: Nmdars In Inhibitory Neuronsmentioning
confidence: 96%
See 2 more Smart Citations
“…The role of NMDARs in developing interneurons has remained elusive. Interneurons express NMDARs, and synaptic NMDARmediated excitatory postsynaptic currents increase robustly between P6 and P8-10 (Zhang and Sun, 2011). Later, interneurons downregulate NMDAR currents (Wang and Gao, 2010), which could explain why NMDARs play no role in the recruitment of feed-forward inhibition by adult thalamocortical inputs (Hull et al, 2009;Ling and Benardo, 1995).…”
Section: Nmdars and Vgccs Mediate Dendritic Growth Triggered By Selecmentioning
confidence: 99%